Estudio descriptivo de la relación entre la autoeficacia y la selección de carrera en los estudiantes de primer ingreso a las carreras del Área Biológica de la modalidad presencial de la UTPL periodo 2016 2017 - Carpio Campoverde, Lyzbeth Vanessa (2018)
Abstract:The present investigation, permitted determine the level of self-efficacy in the career selection in the entering students to qualification of the Biological Area. A quantitative study non-experimental was developed, with descriptive method. The specimen was made in 152 entering students of the Biological Area and two instruments were aplied: the self-efficacy perceived in the careers election of O shea and Feller, and the self-efficacy for learning of Kitsasntas and Zimmerman. The careers of Agricultural and Biochemistry & Pharmacy, have a higher level of self-efficacy with respect to other careers. The dimensions that stand out in a general way in the Biological Area are resolution of external / family conflicts and selection of goals in which the students show some ability, while the dimension in which they have less ability is planning. Recarding the self-efficacy level according to gender, women have a higher score than men, instead of there is no significative difference between both genders.